A tectonic and provenance study of the Chugach-Prince William terrane, Alaska, with specific focus on the Paleogene Orca Group, Using U-Pb dating of detrital zircons - Grimm, William Edward (Carleton Digital Commons, 2015)
The Late Cretaceous to Tertiary Chugach-Prince William (CPW) terrane is exposed for approximately 2,200 km on the southern Alaskan continental margin, and it constitutes one of the largest known subduction-related accretionary complexes in the world. The provenance of the CPW terrane is currently under debate, and two major hypotheses exist for the deposition, accretion, and subsequent tectonic history of the CPW terrane. The first is that the CPW terrane formed south of its present latitude, interacted with the fixed Kula-Farallon ridge to produce ~61-50 Ma near-trench plutonism of the Sanak-Baranof belt (SBB), and was translated to its present position by dextral coast-parallel slip. The other hypothesis is that the CPW terrane formed approximately in its current location, and it interacted with the migrating Kula- Resurrection ridge to form the SBB plutons. This study presents 12 new detrital zircon U- Pb maximum depositional ages (n=2,345) from the flysch of the Paleogene Orca Group in eastern Prince William Sound, Alaska, in order to more fully understand the tectonic history and provenance of the Orca Group. Maximum depositional ages of the Orca Group in eastern Prince William Sound range from 61 Ma to 51 Ma, and samples generally young from inboard to outboard, with the youngest ages on Hinchinbrook Island. These U-Pb data, combined with zircon fission track data, show that distinct, fault-bounded "belts" of Orca Group rocks present in western Prince William Sound do not carry over into eastern Prince William Sound. Precambrian grains exhibit Archean Paleoproterozoic, Mesoproterozoic, and Neoproterozoic populations, which indicate a mixed northern-southern Laurentian source for these grains in the Orca Group. The data from this study, in context with previous detrital zircon data from the CPW terrane, supports the restoration of the CPW terrane to a location south of its present position in the time of deposition during the Late Cretaceous to Paleocene.